Factors associated with early initiation of breastfeeding among children less than 24 months old: the 2019 Ethiopian mini demographic and health survey - Tadele Abate Lucha; Admassu Ketsela Mengistu (BMC, 2022)
Abstract Background The world Health Organization recommended that all mothers be supported to initiate breastfeeding as soon as possible after birth, within the first hour. This study examined the determinants of early initiation of breastfeeding in Ethiopia by using data from the 2019 Ethiopia Mini Demographic and Health Survey. Methods The data for this study was extracted from the 2019 Ethiopia Mini Demographic and Health Survey. A total of 1948 children aged less than 24 months at the time of the survey were included for analysis from the nine regional states and two city administrations. The analysis was carried out in STATA Version 14.2 software using survey commands to account for the complex sample design and apply sampling weights. A manual backward stepwise elimination approach was applied. Result The prevalence of early initiation of breastfeeding in Ethiopia was noted to be 75.2% [95% CI (71.9, 78.5%)]. In the multivariable analysis, mothers who had vaginal deliveries [AOR = 3.02 (95% CI: 1.55, 5.88)] had 3 times higher odds practicing early initiation of breastfeeding compared to mothers who had a cesarian section. Mothers aged between 35 and 49 years [AOR = 2.40, 95% CI: 1.20, 4.49] had 2.4 times higher odds of practicing early initiation of breastfeeding compared to mothers aged below 20 years. In addition, early initiation of breastfeeding was also associated with the region where mothers resided, in particular mothers in Amhara and Somali region, had lower odds of practicing early initiation of breastfeeding as compared with mothers residing in Tigray region. Conclusion Early initiation of breastfeeding in Ethiopia was found to be significantly associated with mode of delivery, mother's age, and region. As a result, raising awareness about early initiation of breastfeeding is especially important for mothers who have had a cesarean section, which could be accomplished with the help of the health extension workforce.